(untitled) (Minerva, 2019)
Jovellanos (1774-1811) often mentions the Graeco-Roman classics. This paper examines the presence of classical tradition in some of his works (the so called literary, as well as part of his Diario), distributing the material in several items: citations of unmentioned Latin authors; Neo-Latin; observations about the study, knowledge or ignorance of Greek or Latin language; mentions of authors or works from Greek literature; references of authors or works from Latin literature; Greek or Roman historical personages; general notes of Graeco-Roman culture.